Patients' expectations and experiences of provided surgery‐related patient education: A descriptive longitudinal study - Katrín Blöndal; Herdís Sveinsdóttir; Brynja Ingadottir (Nursing Open, 2022)
Abstract Aims The aim of this study was to explore the educational expectations and experiences of surgical patients. Design Prospective, longitudinal, descriptive and two‐centre study. Data were collected with questionnaires at the hospital and 6 weeks and 6 months postsurgery. Methods Patients undergoing elective surgery and hospitalized overnight from January to July 2016 answered questions about the content of received pre‐operative and pre‐discharge education, topics they wanted more information on, sources of information, satisfaction with and usefulness of the information and if their recovery was as expected. Results Patients (N = 697, 49% male, mean age 64.1 [SD 12.6] years) perceived the provided education as useful and satisfactory but less so after discharge. Most common topics which they expected more education about were postoperative complications, pain management, fatigue, lack of stamina and expected recovery time. Most patients received information through face‐to‐face teaching (79.7%) and in writing (78.4%). Expectations on recovery were related to patients' satisfaction with the education and how useful they evaluated it.